Penyusunan Kriteria Domestikasi Dan Evaluasi Praktek Pengasuhan Gajah: Studi Di Taman Nasional Way Kambas Kabupaten Lampung Timur - Putri Meytasari; Samsul Bakri; Susni Herwanti (Jurnal Sylva Lestari, 2014)
Sumatran elephants (Elephas maximus sumatranus) is one of the many wild animals been domesticated, but so far there is no criteria for that propose. This research is a prelimenary effort in providing those criteria. This research began in April to May 2013. The first step was to establish the norm of Suitable range of as many as 17 variables required for upholding the elephant life domestication area. The Suitable norm range we determined through an exhausted study of previous researchs or literature available. The next step was to determined the Less Suitable and the Not Suitable norms range for those 17 variables employed, e.i. by deviating by 25% and by 50% from the Suitable norm range respectively. The second step, we employed a Delphi Method in order to validate and refinary the three catagorical norms range of the 17 varibles concerned by mean of asking to some elaphant experts in our country.  We, then applied the deemed criteria to evaluate a practice of ephants management at The Sumatra Elephant Conservation Center (PKG) and the Elephant Response Unit (ERU), Way Kambas National Park. The research results: (1) We obtained the prelimenary criteria as a rubric for Sumatran elephant domestication, and (2) The elephant nurturing practices at PKG and ERU were Suitable, except for the variables of population density, home range and elephant shading. Keywords: domestication criteria, sumatran elephant, practices of elephant nurturing